Infantile spasms with periventricular nodular heterotopia, unbalanced chromosomal translocation 3p26.2 ‐10p15.1 and 6q22.31 duplication - Jones, Kevin (Clin Case Rep, 2016)
Patients presenting with infantile spasms, dysmorphic features, and periventricular nodular heterotopia may benefit from genetic copy number variation microarray, or whole‐exome sequencing to identify candidate genes. This will allow personalized diagnosis and prognostication and the eventual understanding of single and combined gene functions in brain health and disease.